Embodied Labour - Szklarczyk, Justyna | https://orcid.org/0000-0001-6253-7071 (Taylor & Francis, 2026)
In a world where physical labour seems to disappear from dominant public narratives, Embodied Labour offers an in-depth, interdisciplinary analysis of the bodily experiences of work and their significance as elements of European cultural heritage. This collection examines the physical dimension of labour across various European locations – from Estonian oil shale mines, through Norwegian ironworks, to State Agricultural Farms in Poland. Together, the chapters explore how the rhythms of physical labour shaped landscapes, identities, and communities, whilst also addressing issues of representation in museums, literature, and art, and the challenges of conveying bodily experiences to contemporary audiences. The authors challenge linear narratives about the development of work, showing that physical labour has not disappeared but rather changed its character – becoming less visible, more fragmented, and marginalised in public narratives. The volume restores dignity and significance to these experiences, treating the working body not merely as a tool of production but also as a carrier of memory, identity, and knowledge. Embodied Labour is of interest to students and scholars from various disciplines – from history and anthropology, through heritage studies, to philosophy – as well as anyone interested in the cultural, social, and historical dimensions of labour in Europe. Chapter 10 of this book is freely available as a downloadable Open Access PDF at http://www.taylorfrancis.com under a Creative Commons Attribution-Non Commercial-No Derivatives (CC BY-NC-ND) 4.0 International license.